LINKAGES FINANCIAL DISTRESS, GROWTH OPPORTUNITIES, LITIGATION RISK, POLITICAL COST AND ACCOUNTING CONSERVATISM - Darmanto; Karlina Hogiana Suprihadi Putri (STIE St. Pignatelli Surakarta, 2020)
This study aims to examine whether Financial Distress, Growth Opportunities, Litigation Risk and Political Cost Against Accounting Conservatism in Manufacturing Companies on the Stock Exchange in 2016-2018. Population used in this study is manufacturing companies listed on the Indonesia Stock Exchange. The samples used were 75 companies per year with a sampling technique using purposive sampling method. The data used in the form of the company's annual financial statements obtained from www.idx.co.id. Data analysis techniques were performed using multiple regression analysis with the help of SPSS version 16.0 Data analysis of this study uses multiple linear regression which results that the risk of litigation has a positive and significant effect on accounting conservatism, while financial distress, growth opportunities, and political cost do not significantly influence accounting conservatism. This study also shows that the independent variables influence the dependent variable together. Adjusted R2 test results mean that the independent variable affects the dependent variable of accounting conservatism by 35.5%, and the remaining 64.5% is influenced by other factors not tested in this study.